2005
DOI: 10.5194/angeo-23-759-2005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the ionosphere on the altitude of discrete auroral arcs

Abstract: Abstract. The altitude of the maximum luminosity of single, discrete auroral arcs was measured by photometric triangulation from two stations (College and Fort Yukon, Alaska) located 226 km apart on nearly the same magnetic meridian. The average height of the evening aurora decreases smoothly with increasing solar depression angle (sda) from 160 km near 12 • sda to 100 km after 18 • sda. The average height remains constant until around 12 • sda in the morning. This diurnal variation is similar to that of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
(33 reference statements)
3
6
0
Order By: Relevance
“…[3] The finding of an increase in the local nighttime auroral intensity from winter to summer is associated with an increase in the energy of precipitating electrons . This is also confirmed, to some extent, by Deehr et al [2005], who found that the average altitude of the maximum luminosity of evening discrete arcs decreases with increasing solar depression angle. Direct measurements of precipitating particles from FAST have also shown an increase (up to ∼50%) in the premidnight sector [Cattell et al, 2006].…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…[3] The finding of an increase in the local nighttime auroral intensity from winter to summer is associated with an increase in the energy of precipitating electrons . This is also confirmed, to some extent, by Deehr et al [2005], who found that the average altitude of the maximum luminosity of evening discrete arcs decreases with increasing solar depression angle. Direct measurements of precipitating particles from FAST have also shown an increase (up to ∼50%) in the premidnight sector [Cattell et al, 2006].…”
Section: Introductionsupporting
confidence: 77%
“…At other local times, the mean energy increase is smaller (10–15% for the 09:00–15:00 MLT sector) and is consistent with the FAST results [ Cattell et al , 2006] (∼20% in the 06:00–10:00 MLT sector). Deehr et al [2005] reported that the average energy of the precipitating electrons, inferred by the average peak heights of discrete auroral arcs, in the evening twilight (102°–108° SZA) increases with the solar depression angle. Therefore, one can conclude that the increase in the energy flux of precipitating electrons with a decrease in solar illumination is in large part due to the increase in the average energy of precipitating electrons at all local times.…”
Section: Discussionmentioning
confidence: 99%
“…Other workers also used this technique, but applied to two photometers only (e.g. Sandholt et al, 1982;Sigernes et al, 1996;Deehr et al, 2005). Sigernes et al (1996) emphasise that their analysis is restricted to narrow auroral structures.…”
Section: Previous Workmentioning
confidence: 99%
“…However, our altitude of interest in the ionosphere was 100 km, as it is the average auroral altitude (Deehr et al, 2005) and we are interested in looking at auroral data for potential optical signatures. Convection vortices, another manifestation of potential signatures, can be observed by the Super Dual Auroral Radar Network (SuperDARN) which looks at reflections in the F region (150 to 800 km) (Greenwald et al, 1995).…”
Section: Perturbation Travel Timementioning
confidence: 99%